2021
DOI: 10.1177/0021998321993917
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced mechanical properties of carbon nanotube-reinforced magnesium composites with zirconia fabricated by spark plasma sintering

Abstract: This study aims to enhance carbon nanotube (CNT)-reinforced magnesium (Mg) matrix composites fabricated by spark plasma sintering (SPS). Ultrasonic treatment with organic solvent (DMAc) and dispersant (K2CO3) were used for the processes to make each CNT apart. Nano-order ceramic powders of zirconia (ZrO2) were found to be effective to keep uniform dispersion of CNT in Mg matrix. Low melting point metals such as Sn were added to fill voids and cracks in the composites. Post-SPS rolling was also employed aiming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…The results of artificial neural network (ANN) were compared with support vector regressor and random forest method, and promising output was obtained from ANN models. Tsukamoto [12] used spark plasma sintering to create CNT-added magnesium composites. It was asserted that obtaining composites with superior properties was challenging due to low dispersibility and developing accumulations of CNT, as well as the existence of void spaces and fractures in the composites.…”
Section: Introductionmentioning
confidence: 99%
“…The results of artificial neural network (ANN) were compared with support vector regressor and random forest method, and promising output was obtained from ANN models. Tsukamoto [12] used spark plasma sintering to create CNT-added magnesium composites. It was asserted that obtaining composites with superior properties was challenging due to low dispersibility and developing accumulations of CNT, as well as the existence of void spaces and fractures in the composites.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] CNT is a seamless tube in which a honeycomb-structured layer is rolled into a cylindrical shape, and depending on the number of carbon layers, CNT can be classified into two categories, single-walled carbon nanotube (SWCNT) and multi-walled carbon nanotube (MWCNT). [4][5][6][7][8] Carbon nanotube can be a potential reinforcement of high-performance metal matrix composites (MMCs) due to their variety of excellent properties. [9][10][11][12] However, it has been reported that there is difficulty in dispersing CNT uniformly in the matrix.…”
Section: Introductionmentioning
confidence: 99%
“…13 CNT is a seamless tube in which a honeycomb-structured layer is rolled into a cylindrical shape, and depending on the number of carbon layers, CNT can be classified into two categories, single-walled carbon nanotube (SWCNT) and multi-walled carbon nanotube (MWCNT). 48…”
Section: Introductionmentioning
confidence: 99%